Concurrent nicotine exposure to prenatal alcohol consumption alters the hippocampal and cortical neurotoxicity. Issue 1 (January 2020) - Bhattacharya, Dwipayan; Fujihashi, Ayaka; Majrashi, Mohammed; Bloemer, Jenna; Bhattacharya, Subhrajit; Buabeid, Manal; Escobar, Martha; Moore, Timothy; Suppiramaniam, Vishnu; Dhanasekaran, Muralikrishnan
Abstract: Aims: This study investigated the neurotoxic effects of prenatal alcohol and nicotine exposure in the cortex and hippocampus of rodents. Main methods: Behavioral alterations, electrophysiological changes, and biochemical markers associated with cholinergic neurotransmission, neural oxidative stress, mitochondrial function, and apoptosis were evaluated. Key findings: Prenatal alcohol exposure induced the generation of ROS, nitrite and lipid peroxide, decreased mitochondrial Complex-I and IV activities, increased Caspase-1 and 3 activities, had no effect on cholinergic neurotransmission, increased expression of PSD-95, decreased LTP and decreased performance on spatial memory tasks. However, nicotine exposure, in addition to alcohol exposure, was found to mitigate the negative effects of alcohol alone on ROS generation and spatial memory task performances. Furthermore, we also studied the role of ILK in prenatal alcohol and nicotine exposure. Significance: Prenatal Smoking and/or drinking is a major health concern around the world. Thus, our current study may lead to better insights into the molecular mechanisms of fetal alcohol and nicotine exposure on the developing offspring. Abstract : Neuroscience; Aging; Mitochondrial function; Oxidative stress